Resonant grating of magnetodielectric resonance nanospheres - Kozar, A.I. (Radiotekhnika, 2017)
The design method, based on integral equations of macroscopic electromagnetics, is proposed for studying the electromagnetic waves scattering by the limited resonance grating, made of small resonance magnetodielectric spheres, located in the magnetodielectric environment. The analytical investigations of fields scattered by the resonance grating are presented.